Varieties of Code Used by a Mixed Culture Student - Theodoron Fredrik (Kata Kita: Journal of Language, Literature, and Teaching, 2020)
Codes or dialects are the most important factor in society to communicate every day. In a society, a person acquires and learns the particular code to get along with the community. It becomes interesting when a person can speak more than one code. The purpose of this study is about the varieties of code used by a person on several occasions with different people and codes/dialects. This study used qualitative approach. The results show that there were five codes that the subject used and the most frequent code spoken by the subject was Kupangnese. It can be concluded that the participants whom the subject talked to influenced the Kupangnese code to occur more.    Keywords: variety, code, mixed culture